Gymnastic Motivation Survey at The Shelter of The Indonesian Embassy in Kuala Lumpur - Santi, Dwi Gansar (Universitas Negeri Semarang, 2020)
The aim is to find out how much motivation Indonesian workers are towards the gymnastic at the Indonesian Embassy in Kuala Lumpur. The research method is descriptive quantitative research. The population of this research is 76 Indonesian workers residing in the shelter. The data analysis used descriptive percentage. The results showed the average score of motivation in following gymnastic was 25.64 with a percentage level of 80.13% categorized as high. This motivation appears to be influenced by several supporting indicators, including: the average physiological indicator is 3.29 with a percentage level of 82.25% categorized as high, the average safety indicator is 3.84 with a percentage level of 76.80% is categorized as high, the average social indicators is 7.53 with a percentage level of 94.13% being categorized as very high, the average self-esteem indicator is 4.45 with a percentage level of 74.16% being categorized as high, the average self-actualization indicator is 6.51 with a percentage level of 72.33% being categorized as high. Aerobic participants have high motivation to maintain health and physical fitness.